Faktor-Faktor Keberhasilan Implementasi Kurikulum Pendidikan Seksual Pada Remaja di Sekolah : Literature Review - Afifah Shafa Ulya; Evi Martha (Jurnal Ners, 2026)
Implementation of Comprehensive Sexuality Education (CSE) in schools is an essential strategy to improve adolescent reproductive health and prevent risk behaviors such as adolescent pregnancy and sexually transmitted infections. The effectiveness of this curriculum is strongly influenced by supporting and inhibiting factors at both systemic and practical levels. This literature review aims to identify the determinants of successful implementation of sexual education curricula for adolescents in schools. A literature review method was applied to 13 journal articles from various countries (Indonesia, Zambia, Nepal, the Philippines, Malaysia, and the United States) obtained from four digital databases (Researchgate, Google Scholar, PubMed, and ScienceDirect) using keywords related to sexuality education, curriculum implementation, and determinants. The analysis identified five main determinants of successful implementation: political support and local authority legitimacy, school principal leadership, teacher competence and values clarification, school-parent partnership, and participatory pedagogical methods involving youth voice. The main barriers found were cultural taboos, limited resources, and weak monitoring and evaluation mechanisms. The study concludes that successful CSE implementation requires cross-sector synergy among policymakers, schools, teachers, and families.